MAINSTREAM AND SPECIAL EDUCATION TEACHERS’ IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION - Mariyam Shareefa; Rohani Hj Awg Mat Zin; Nor Zaiham Midawati Abdullah; Rosmawijah Jawawi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study examines the difference between mainstream teachers and Special Education Needs (SEN) teachers’ implementation of Differentiated Instruction (DI) in Maldivian schools. A total of 64 teachers (32 mainstream teachers and 32 SEN teachers) were randomly selected, and data were collected using survey (N=64) and classroom observation (N=8). Independent sample t-test was adopted to analyse survey data, while mean scores of the rating scale were used to analyse observation checklist. Findings revealed that there is no significant difference between the two groups of teachers’ implementations. Both mainstream teachers and SEN teachers adopt DI at a very low level. Hence, findings suggest that despite the special training, and the importance of DI to SEN students, SEN teachers did not implement DI at any higher level than mainstream teachers. Therefore, a review of training programs conducted for both mainstream teachers and SEN teachers are found necessary.